An Investigation of CYP2D6 Genotype and Response to Metoprolol CR/XL During Dose Titration in Patients With Heart Failure: A MERIT‐HF Substudy. Issue 3 (30th September 2013) - Batty, J A; Hall, A S; White, H L; Wikstrand, J; de Boer, R A; van Veldhuisen, D J; van der Harst, P; Waagstein, F; Hjalmarson, Å; Kjekshus, J; Balmforth, A J
<x xml:space="preserve">Abstract</x> To explore the pharmacogenetic effects of the cytochrome P450 (CYP)2D6 genotype in patients with systolic heart failure treated using controlled/extended‐release (CR/XL) metoprolol, this study assessed the CYP2D6 locus for the nonfunctional *4 allele (1846G>A; rs3892097) in the Metoprolol CR/XL Randomised Intervention Trial in Congestive Heart Failure (MERIT‐HF; n = 605). Participants were characterized as extensive, intermediate, or poor metabolizers (EMs, IMs, or PMs, respectively), based on the presence of the CYP2D6*4 allele (EM: *1*1, 60.4%; IM: *1*4, 35.8%; and PM: *4*4, 3.8%). Plasma metoprolol concentrations were 2.1‐/4.6‐fold greater in the IM/PM groups as compared with the EM group (P < 0.0001). Metoprolol induced significantly lower heart rates and diastolic blood pressures during early titration, indicating a CYP2D6*4 allele dose–response effect (P < 0.05). These effects were not observed at maximal dose, suggesting a saturable effect. Genotype did not adversely affect surrogate treatment efficacy. CYP2D6 genotype modulates metoprolol pharmacokinetics/pharmacodynamics during early titration; however, the MERIT‐HF‐defined titration schedule remains recommended for all patients, regardless of genotype. Clinical Pharmacology & Therapeutics (2014); 95 3, 321–330. doi:10.1038/clpt.2013.193